Adsorption of Pb(II) on Calix[4]arene Derivatives: Kinetics and Isotherm Studies - Busroni Busroni; Dwi Siswanta; Jumina Jumina; Sri Juari Santosa; Chairil Anwar (Indonesian Journal of Chemistry, 2022)
This study aims to investigate the application of two calix[4]arene derivatives named 5,11,17,23-tetra-(t-butyl)-25,26,27,28-tetrahydroxycalix[4]arene (TBCA) and 5,11,17,23-tetra-(t-butyl)-26,27,28-tribenzoyloxycalix[4]arene (TBMTCA) as adsorbents of Pb(II) from aqueous solution in a batch system. Adsorption was carried out by varying pH solution, exposure time, and concentration. The kinetics was evaluated based on the adsorption in various exposure times using the Lagergren and Ho equations, while the isotherms were analyzed based on the adsorption in various Pb(II) concentrations using the Langmuir and Freundlich equations. Furthermore, the isotherm model showed the Pb(II) adsorption of TBCA and TBMTCA followed Langmuir model with a capacity of 137.29 and 128.46 mg/g, respectively. Based on the adsorption capacity, both adsorbents are the potential for the removal of heavy metal cations from polluted water.